The efficient synthesis and purification of 2′3’- cGAMP from Escherichia coli - Kulkarni, Rohan; Maranholkar, Vijay; Nguyen, Nam; Cirino, Patrick C.; Willson, Richard C.; Varadarajan, Navin (Frontiers in Microbiology, 2024)
Agonists of the stimulator of interferon genes (STING) pathway are being explored as potential immunotherapeutics for the treatment of cancer and as vaccine adjuvants for infectious diseases. Although chemical synthesis of 2'3' -cyclic Guanosine Monophosphate-Adenosine Monophosphate (cGAMP) is commercially feasible, the process results in low yields and utilizes organic solvents. To pursue an efficient and environmentally friendly process for the production of cGAMP, we focused on the recombinant production of cGAMP via a whole-cell biocatalysis platform utilizing the murine cyclic Guanosine monophosphate-Adenosine monophosphate synthase (mcGAS). In E. coli BL21(DE3) cells, recombinant expression of mcGAS, a DNA-dependent enzyme, led to the secretion of cGAMP to the supernatants. By evaluating the: (1) media composition, (2) supplementation of divalent cations, (3) temperature of protein expression, and (4) amino acid substitutions pertaining to DNA binding; we showed that the maximum yield of cGAMP in the supernatants was improved by 30% from 146 mg/L to 186 ± 7 mg/mL under optimized conditions. To simplify the downstream processing, we developed and validated a single-step purification process for cGAMP using anion exchange chromatography. The method does not require protein affinity chromatography and it achieved a yield of 60 ± 2 mg/L cGAMP, with <20 EU/mL (<0.3 EU/µg) of endotoxin. Unlike chemical synthesis, our method provides a route for the recombinant production of cGAMP without the need for organic solvents and supports the goal of moving towards shorter, more sustainable, and more environmentally friendly processes.